Level Of Physical Activity And Pain Scale In Elderly At Posyandu Lansia Mekar Sari Surabaya - Sampouw, Adela S; Dian, Arief; Jong, FX Himawan H. (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction : The increasing number of elderly life expectancy has caused health issues. The majority of elderly have dealt with a pain issue. furthermore, the pain can affect their physical activities. Aim : This study aimed to analyze the relationship between elderly physical activity level with pain scale. Methods : An observational analytical study with a cross sectional approach was used for the study. The respondents were elderly people who visited Posyandu Lansia Mekar Sari Surabaya from 29th July until 11th October in 2017. Data of physical activities were collected by interviewing the respondents with questions taken from International Physical Activity Questionnaire (IPAQ). They were also asked to point which scale matched their pain problem best on the Numeric Rating Scale (NRS) card. The results of the questionnaire was examined by Rank Spearman Test. Result : There was no significant relationship found in between the two variables (p=0,328). Conclusion : The elderly people at Posyandu Lansia Mekar Sari Surabaya were active and mostly has mild and moderate scale of pain.